EFFECTS OF ZEOLITE AND LIQUID WASTE OF MSG (MONOSODIUM GLUTAMATE) ON PRODUCT OF NILAM PLANT (Pagostemon Cablin BENTH) IN ULTISOLS - Kusumastuti, Any; Parapasan, Jonathan; Riniarti, Dewi (Jurnal Zeolit Indonesia, 2007)
Ultisols is soil which predominate area in Lampung Province. This soil is rather acid until acid reaction, low in cation exchange capacity (CEC) and organic materials content so that cause inefficient of fertilization. Zeolite is a available and potential mining products and it is abundant available in Lampung Province. It can also to improve CEC of soil so that the absorption of soil to fertilizer can be increased. Besides, it has a high negative charges, so that it can also absorbed of nutrients and discharged it slowly. A liquid waste of MSG is an agroindustrial waste which enough potential. The waste contains the high enough organic materials and compound, especially nitrogen. Low of organic materials at Ultisols, caused needed an input to this management, for example combination usage of zeolite and liquid waste MSG. Nilam is plantation crop which have a good enough prospect, and have potency as state resource of stock-exchange and also can open the new employment. This research arranged in garden of Lampung State Polytechnic, Hajimena district, with Ultisols, itâs started from July until January 2006. The research was conducted on factorial method with randomized block design, consist of 2 factors, zeolite application Z0 (0;1,5; 3,0; 4,5 ton/ha), and liqud waste of MSG (0; 2000; 4000, 6000 l/ha). The data were analysed and then, if the F-test is significantly different we continued with mean of BNT test. Using zeolite at 1,5 ton/ha level increased the plant fresh weight and at 3,0 ton/ha level improved the plant dry weight. Using liquid waste of MSG at of 6000 l/ha level, the highest result of fresh weight and dry weight of plant. Interaction of zeolite and liquid waste of MSG at combination of 4,5 ton/ha and 2000 l/ha showed the highest result on fresh weight and dry weight of root. The combination of 3,0 ton/ha and 6000 l/ha of zeolite and liquid waste of MSG showed the highest result on the ratio of root weight.